Introduzione - Funes, Atelier (Funes. Journal of narratives and social sciences, 2017)
In the mid-twentieth century, Wilhelm Schapp stated: « We human beings are always involved in stories. Everyone is always part of every story in which is involved. “History” and “being involved in stories” are closely related to the point that, even in thought, it is likely impossible to separate them. » Recently, a consistent trend of openness towards narrative analysis has emerged in social sciences. This renewed research perspective integrates a tradition of narratological studies that was originally oriented to the analysis of texts and artistic products, literature, movies, television, and so on. This phenomenon, defined as narrative turn , apart from connecting traditionally unrelated disciplines to the narratological analysis - such as history, sociology, psychology, politics, economics and marketing - is emerging as a unifying ground for the conventional distinctions between fields of knowledge.